Strategies towards a more sustainable aviation: A systematic review. (1st February 2023) - Afonso, Frederico; Sohst, Martin; Diogo, Carlos M.A.; Rodrigues, Simão S.; Ferreira, Ana; Ribeiro, Inês; Marques, Ricardo; Rego, Francisco F.C.; Sohouli, Abdolrasoul; Portugal-Pereira, Joana; Policarpo, Hugo; Soares, Bruno; et al.
Abstract: As climate change is exacerbated and existing resources are depleted, the need for sustainable industries becomes ever so important. Aviation is not an exception. Despite the overall carbon dioxide emissions related to the aviation sector accounts for 2%–4% currently, forecasts for air travel indicate an annual growth of 3%–5% and other industries present more potential to reduce carbon emissions once they recur to an increasing use of renewable energies. This option is more difficult in aeronautics since an efficient and lighter energy storage system is required and the current state of the art in battery technology is far from the specific energy densities of fossil fuels and its production is not friendly to the environment. Thus, a herculean effort to integrate several promising mitigation strategies in an efficient way is required. In this paper, a review of the most upfront solutions towards greener aviation is presented and categorized as follows: concepts of operations, energy storage, propulsion systems, aerodynamics, structures, materials, and manufacturing processes. In the end, potential synergies between the different technologies to achieve green aviation are proposed.